Study of BaCe0.4Zr0.4Y0.2O3-δ/BaCe0.8Pr0.2O3-δ (BCZY/BCP) bilayer membrane for Protonic Conductor Solid Oxide Fuel Cells (PC-SOFC). (14th February 2020) - Basbus, J.; Arce, M.; Troiani, H.; Su, Q.; Wang, H.; Caneiro, A.; Mogni, L.
Abstract: This paper address the blocking of the electronic conductivity for a BaCe0.8 Pr0.2 O3-δ (BCP) material due to the addition of a BaCe0.4 Zr0.4 Y0.2 O3-δ (BCZY) thin layer. Barium cerates (BCP and BCZY) show interesting features as electrolytes for Proton Conducting Solid Oxide Fuel Cells (PC-SOFC). BCP perovskite displays good mechanical properties associated to its sintering capability, typically proposed as a possible electrolyte. However, this compound shows poor CO2 tolerance above 500 °C and presents mixed conductivity under wet synthetic air. Protonic transport is the main feature of BCZY perovskite and it presents an excellent CO2 tolerance. However, the drawback of this compound is its high grain boundary resistance. In this work, a BCZY film was grown by Pulsed Laser Deposition (PLD) on BCP in order to block its electronic conductivity and improve CO2 tolerance. From the electrochemical characterization of materials, it is proposed that BCP dominates transport mechanisms on the BCZY/BCP bilayer membranes under wet synthetic air and wet diluted hydrogen. Our measurements confirm that the BCZY film blocks the electronic conductivity of BCP under wet synthetic air and protects it from CO2 -containig atmospheres. Due to this set of properties, the BCZY/BCP bilayer membrane represents a possible candidate as electrolyte for PC-SOFC operating between 400 and 600 °C. Highlights: ∼1 μm film BCZY was grown by PLD and it shows fully dense columnar microstructure. BCP dominates transport mechanisms on bilayer membrane under O2 and H2 atmospheres. BCZY film blocks electronic conductivity of BCP under wet O2 atmosphere. BCZY/BCP is a potential electrolyte for PC-SOFC operating between 400 and 600 °C.